1997
DOI: 10.1021/ef970076p
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Hydrogen Mobility in Coal Using a Tritium Tracer Method. 1. Hydrogen Exchange Reaction of Coal with Tritiated Water

Abstract: The hydrogen exchange of coals with water was investigated using a tritium tracer method to estimate the mobility of hydrogen in coals. The reactions at several temperatures between 50 and 300 °C were carried out using a glass batch reactor and a pulse flow reactor, respectively. At lower temperatures, the ratio of hydrogen exchange of coal with water increased with a decrease in rank of coals and tended to change with respect to the content of functional groups such as hydroxyl group, thiol, amino group, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Nature of Mobile Coal Hydrogen. It is a well-established fact that exposing hydroxyl groups in coal to liquid or gaseous D 2 O can deuterate them. Figure shows the change in the IR spectra of deuterated YL coal. The peak around 2500 cm -1 grows with the length of exposure, while the peak due to OH groups around 3400 cm -1 diminishes in size.…”
Section: Resultsmentioning
confidence: 99%
“…Nature of Mobile Coal Hydrogen. It is a well-established fact that exposing hydroxyl groups in coal to liquid or gaseous D 2 O can deuterate them. Figure shows the change in the IR spectra of deuterated YL coal. The peak around 2500 cm -1 grows with the length of exposure, while the peak due to OH groups around 3400 cm -1 diminishes in size.…”
Section: Resultsmentioning
confidence: 99%
“…In the present paper, we review our recent studies concerning the hydrogen exchange reaction of various coals with tritiated water and gaseous hydrogen to estimate the amounts of hydrogen in functional groups of coals. In the pressurized system with tritiated water using the batch reactor, aromatic hydrogen around the functional groups in coal can be determined. This study is the original contribution for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…As reported recently, tritium tracer methods are very effective for the quantitative tracing of hydrogen behavior of coal and tetralin during coal liquefaction in a batch reactor. Further, tetralin is known to be a simple and good solvent in the coal liquefaction process and can be taken as a typical model compound representing the aromatic compounds in distillate fuels, especially in fcc-LCO. Recently, we reported that the hydrogen mobility of tetralin can be elucidated using a flow reactor .…”
Section: Introductionmentioning
confidence: 99%